2002
DOI: 10.1086/344532
|View full text |Cite
|
Sign up to set email alerts
|

myotilin Mutation Found in Second Pedigree with LGMD1A

Abstract: Limb-girdle muscular dystrophy 1A (LGMD1A [MIM 159000]) is an autosomal dominant form of muscular dystrophy characterized by adult onset of proximal weakness progressing to distal muscle weakness. We have reported elsewhere a mutation in the myotilin gene in a large, North American family of German descent. Here, we report the mutation screening of an additional 86 families with a variety of neuromuscular pathologies. We have identified a new myotilin mutation in an Argentinian pedigree with LGMD1 that is pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
1
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(62 citation statements)
references
References 27 publications
4
54
1
3
Order By: Relevance
“…27 The presence of many rimmed vacuoles was compatible with the pattern observed in some forms of muscular dystrophy such as LGMD2G 28 and LGMD1A. 29 Telethonin was present in a normal sarcomeric distribution in the muscle (Figure 4b), which does not allow to rule out; however, a possible interaction between the protein product of the LGMD1G gene and this sarcomeric protein.…”
Section: Discussionsupporting
confidence: 67%
“…27 The presence of many rimmed vacuoles was compatible with the pattern observed in some forms of muscular dystrophy such as LGMD2G 28 and LGMD1A. 29 Telethonin was present in a normal sarcomeric distribution in the muscle (Figure 4b), which does not allow to rule out; however, a possible interaction between the protein product of the LGMD1G gene and this sarcomeric protein.…”
Section: Discussionsupporting
confidence: 67%
“…If so, they may act synergistically to strengthen the interaction. Recently, four single amino acid substitutions in the Nterminal region of myotilin (S55F, T57I, S60C, and S60F) were shown to cause myofibrillar myopathy and/or LGMD1A (Hauser et al, 2000;Hauser et al, 2002;Selcen and Engel., 2004). The fact that deletion of the first 78 N-terminal residues of myotilin abrogated binding to FATZ-1 indirectly suggested that the N-terminal region of myotilin is important for binding.…”
Section: Discussionmentioning
confidence: 99%
“…Myotilin is able to crosslink actin filaments and to critically affect the assembly of sarcomeres (Salmikangas et al, 2003). Its importance in the maintenance of muscle integrity is further supported by the recent observation that pathogenic mutations in the myotilin gene cause a subset of myofibrillar myopathies and limb girdle muscular dystrophy (LGMD) type 1A that are characterized by streaming of Z-discs and degeneration of myofibers (Hauser et al, 2000;Hauser et al, 2002;Selcen and Engel, 2004). FATZ-1 is another newly characterized 32 kDa protein with no canonical structural motifs (Faulkner et al, 2000;Frey et al, 2000;Takada et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The two other family members, myotilin and myopalladin, are both expressed in striated muscle and localize to the Z-disc (Salmikangas et al, 1999;Bang et al, 2001). Mutations in the myotilin gene have been implicated in a human limb girdle muscular dystrophy, indicating that this family member is required for the maintenance of a normal, functional sarcomeric cytoskeleton (Hauser et al, 2000;Hauser et al, 2002;Salmikangas et al, 2003). The third family member, myopalladin, binds to nebulin (in skeletal muscle) and nebulette (in cardiac muscle), and might have a crucial function in linking these cytoskeletal proteins to the Z-line (Bang et al, 2001;Ma and Wang, 2002).…”
Section: Introductionmentioning
confidence: 99%